Automation and the office worker, 1961 (London, 1961)
1961 1961-70 "Automation and the office worker, 1961" [BW0164], 1961, Trades Union Congress Recruitment leaflet from the Clerical and Administrative Workers' Union focussing on the impact of computers on office work.